Sensorless PMSM Control using Fifth Order EKF in Electric Vehicle Application - Nanda Avianto Wicaksono; Bernadeta Wuri Harini; Feri Yusivar (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
This paper is intended to design a controller and an observer of a sensorless PMSM (permanent magnet synchronous motor) in electric vehicle application. The controller uses the field orientation control (FOC) method and the observer type is the fifth order extended Kalman filter (EKF). The designed controller and observer are tested by varying the elevation angle of the route that is several times abruptly changed. The simulation result shows that the designed controller and observer can respond to the elevation angles given.